Planning of the Clean Water Distribution System Pipeline at Griya Arwana Lestari Housing, Merauke Regency - Utary Chitra; Doloksaribu Abner; Andang Pasalli Daud; Hairulla Hairulla; D Putra Dimas (E3S Web of Conferences, 2021)
Griya Arwana Lestari Housing Merauke Regency is one of the housing estates located in the area around the Merauke coast. The majority of residents of Griya Arwana Lestari housing use rainwater sources and buy water from water tanker trucks for their clean water needs. When the dry season arrives, the price of water from tanker trucks is quite expensive, making it difficult for residents of Griya Arwana Lestari housing to get clean water. So it is necessary to plan a clean water supply network system. The purpose of this study is to find out how much the discharge needs of clean water in Griya Arwana Lestari housing and find out what the diameter of the main pipe and secondary pipe are used. The method used is qualitative and quantitative based on field observations and counting the number of occupants in sustainable arowana housing then analyzing the need for clean water and then determining the diameter of the main pipe and secondary pipe. The results in this study are the required discharge in the housing is 3,973 l/s and for the main pipe diameter is 4 inches and for the secondary pipe 1 inch.